Influence of Envelope Design in the Optimization of the Energy Performance of a Multi-family Building. (March 2017) - Ferrara, Maria; Sirombo, Elisa; Monti, Alberto; Fabrizio, Enrico; Filippi, Marco
Abstract: In Europe, the recast of the Directive on the Energy Performance of Building and the consequent Zero Energy Buildings objective that has to be reached for all new buildings by 2020, lead designers to re-think building design as a complex optimization problem aimed at identifying the most effective strategies to improve building performance.These strategies can help reducing not only the climate change effect, but also the risk of energy poverty for low-income households. This work is intended to apply a simulation-based optimization methodology for optimizingthe energy performance of a multi-family building for social housing. The method combines the use of TRNSYS ® withGenOpt ® . A typical floor of a real case study was modeled and the impacts of the variation of several design parameters on the heating and cooling demand wereassessed.The optimization lead to reduce the primary energy demand of a floor by 36%. The resulted differences in performance and energy rating between flats were analyzed.